Overview of Available Functioning Data in Switzerland: Supporting the Use of Functioning as a Health Indicator Alongside Mortality and Morbidity - Beatriz Moreira; Jsabel Hodel; Melissa Selb; Melissa Selb; Jiin Kim; Carolina Fellinghauer; Jerome Bickenbach; Jerome Bickenbach; Carla Sabariego; Carla Sabariego; Carla Sabariego (Frontiers Media S.A., 2024)
ObjectivesTo identify official sources that routinely collect data on functioning in Switzerland, to provide an overview of the existing data and its comparability, and to assess the extent to which the data is suitable for developing a functioning metric and indicator.MethodsData sources were identified through an iterative search. Standardized rules were applied to map the functioning information assessed by the sources using a current WHO functioning and disability survey as a reference framework for the content comparison.ResultsFour sources were identified: the Swiss Survey of Health, Ageing and Retirement in Europe (SHARE), the Swiss Health Survey (SHS), the Lausanne cohort 65+ (Lc65+), and the Swiss Household Panel (SHP). All tools addressed sleep functions, energy level, emotional functions, and sensation of pain. Additionally, nine functioning categories were common across three sources.ConclusionPopulation data sources in Switzerland routinely collect comparable functioning data, which can serve as the basis for creating a functioning indicator. Among others, this indicator is relevant to complement mortality and morbidity data and to support both the estimation of rehabilitation and long-term care needs.